Defining a control point for the South African abattoir hygiene management system. (2015) - Govender, Reuben
The hygiene management system (HMS) was regulated for South African red meat and poultry abattoirs in mid-2000. It is a basic food safety management system. The HMS requires identification of control points (CPs) where critical limits must be established and control measures set in place. However, a CP has not been defined in legislation and no guidelines are available on how to identify them. Given this gap, the development of meaningful control measures may present a challenge to implementers of the HMS. A conceptual analysis of CPs within the context of food safety was done in relation to ISO 22000:2005, SANS 10330:2007, ISO 10049:2011 and HMS standards. This was done to formulate a meaningful definition for HMS-based CPs because they are a central feature of food safety systems in general, towards providing assurance of safe food. A definition was presented for a CP within the context of the HMS in this paper as well as how it relates to control in comparison with contemporary food safety systems. Results may be used to inform HMS implementation guidelines for abattoirs.